Insecticidal and Repellent Activity of Fatty Acids Derived from Ocimum americanum (Lamiaceae) Plant Extracts against Culex quinquefasciatus Mosquitoes (Diptera: Culicidae) - R, Kamesh; K, Kaniselvam; V, Naveen; P, Ramakrishnan; B, Ranjithkumar; S, Sethu Akash; Rajan, Subala Subramanian Panchuravindra (Free Radicals and Antioxidants, 2025)
Background: Mosquito control efforts are increasingly challenged by the growing resistance to synthetic insecticides. Plant-based insecticides offer a promising alternative for biological control. This study assesses the adulticidal potential of Ocimum americanum extracts against and Culex quinquefasciatus. Materials and Methods: Leaves of O. americanum extracted using hexane, ethyl acetate, and methanol in a Soxhlet apparatus. The extracts were characterized by TLC and GC-MS, and evaluated for antioxidant (DPPH, hydroxyl, ABTS), antimicrobial, and larvicidal activities against C. quinquefasciatus following standard protocols. Larvicidal toxicity was analyzed using probit analysis to determine LC₅₀ and LC₉₀ values. Bioactive compounds identified by GC-MS were further subjected to molecular docking studies to predict protein-ligand interactions. Results: The hexane extract showed the greatest efficacy against C. quinquefasciatus, with LC₅₀ and LC₉₀ values of 4.714 mg/ml (2.8732-6.6121) and 7.436 mg/ml (5.361-12.370) for C. quinquefasciatus, respectively. The plant extracts showed elevated antioxidant activity, as indicated by higher values in the DPPH (55%), ABTS (83%), and hydrogen peroxide (80%) assays. The plant extracts has the high antimicrobial activity with E. coli (32.3%), Klebsiella (37.2%), and Streptococcus sp. (46%). TLC analysis of the hexane extract showed the various spots that are analyzed by GC-MS with 25 compounds. The ligands derived from O. americanum were docked with the dengue virus 3DXL protein using the PyRx platform. Prior to docking, cofactors, water molecules, and existing ligands were removed using Molegro Molecular Viewer. O. americanum ligands were docked with the dengue virus 4FD6 protein using AutoDock 4.2, and the corresponding complexes were also examined using PyMOL. Conclusion: Overall, these findings indicate that O. americanum leaf extracts hold promise as an eco-friendly option for mosquito control.
Keywords: Ocimum americanum; Antimicrobial; Antioxidant; GC-MS; Larvicidal